Penyuluhan ASI Ekslusif Pada Ibu Yang Memiliki Anak Bayi (0-6 Bulan) Di Desa Sipungguk Kecamatan Salo Kabupaten Kampar - Batubara, Hamidah sari; Andriani; Wahyuni, Rika Sri (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2025)
Breast milk is undeniably the best food for babies, but unfortunately, many breastfeeding mothers have forgotten the benefits of breastfeeding. They have allowed their babies to become accustomed to breastfeeding from a substitute, even though only a small number of babies actually use bottles or formula. If this continues, it will undoubtedly pose a serious threat to efforts to preserve and increase the use of breast milk. Nutritional insecurity in infants is caused not only by inadequate food intake but also by the widespread substitution of breast milk for bottle-fed milk in ways and amounts that do not meet their needs. This is a sign of negative social and cultural changes from a nutritional perspective. Infant growth and development are largely determined by the amount of breast milk they receive, including the energy and other nutrients contained therein. Breast milk alone, without other foods, can meet growth needs until approximately four months of age. After that, breast milk serves solely as a primary source of protein, vitamins, and minerals for infants receiving supplementary foods, which primarily consist of rice. Research conducted at the Pediatric Consultation Bureau at Gadjah Mada University Hospital in Yogyakarta showed that 50.6% of children were breastfed up to one year of age. The 1994 Indonesian Children's Health Survey (SKDI) report indicated that 47% of mothers exclusively breastfed their babies, while the target for the sixth five-year plan was 80%. The purpose of this community service program was to provide exclusive breastfeeding education to mothers of infants. The results of this community service program resulted in a greater understanding of the importance of exclusive breastfeeding for their babies.